Benchmarking w procesie restrukturyzacji przedsiębiorstwa - Kowalak, Robert (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
This article presents using the bechmarking in a corporate restructuring process. This tool assisting management permits to determine the trend and the area of corporate restructuring guaranteeing the success of a company. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1175, s. 148-155